Educational resistance. Issue 5 (16th April 2023) - Bojesen, Emile
Abstract: Educational resistance is, here, examined in two of its possible inflections. First, as resistance to educational imposition. Second, as a form of resistance which might itself be educational. Jean-François Lyotard's reflections on 'anamnesic resistance' are developed in the context of educational thought, and then read up against proposals for philosophically informed educational reform by Bernard Stiegler. Stiegler's approach, based in part on a critique of Lyotard, is called in to question, both in terms of its reading of Lyotard and the impositional educational logic it follows. Additionally, this article incorporates a novel application of a practice-as research methodology, in aid of illuminating and exemplifying the central dimensions of its argument, utilising sound as a means of philosophical research and 'anamnesic resistance'.